1966
DOI: 10.1002/anie.196603851
|View full text |Cite
|
Sign up to set email alerts
|

Specification of Molecular Chirality

Abstract: The topological analysis of chiral molecular models has provided the framework of a general system for the specification of their chirality. The application, made in and bejore 19S6, of this system to organic-chemical configurations is generally retained, but is redefined with respect to certain types of structure, largely in the light of experience gained since 1956 in the Beilstein Institute and elsewhere. The system is now extended to deal, on the one hand, with organic-chemical conformations, and, on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
556
0
10

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,773 publications
(580 citation statements)
references
References 39 publications
14
556
0
10
Order By: Relevance
“…On the other hand complex 2 crystallized together with a solvate water molecule and only one enantiomer could be found in the chiral space group P2 1 . The absolute configuration R Ru could be determined according to CIP convention [48], the Flack parameter is 0.01(5). The molecular structures of the studied complexes were directly compared to that of the benzene derivative [Ru( 6 -C 6 H 6 )(pic)(Cl)] defined previously (Ref.…”
Section: Synthesis Characterization and X-ray Diffraction Analysis Omentioning
confidence: 99%
“…On the other hand complex 2 crystallized together with a solvate water molecule and only one enantiomer could be found in the chiral space group P2 1 . The absolute configuration R Ru could be determined according to CIP convention [48], the Flack parameter is 0.01(5). The molecular structures of the studied complexes were directly compared to that of the benzene derivative [Ru( 6 -C 6 H 6 )(pic)(Cl)] defined previously (Ref.…”
Section: Synthesis Characterization and X-ray Diffraction Analysis Omentioning
confidence: 99%
“…For example, the ring carbons of Phe and Tyr lying in the plane with the smaller χ 2 torsion angle are designated as C δ1 and C ε1 . Indicated for reference in parentheses are the pro-R/pro-S designations for prochiral tetrahedral groups (with only the pro-R indicated as 'R') [25,26] and the E/Z designations for planar groups [27,28]. signments relative to the χ 2 torsion angle is needed to define the specific atom designators 1 and 2.…”
Section: Notation For Assignment Ambiguitiesmentioning
confidence: 99%
“…The phosphorus-bound oxygens are named O3′, O5′, OP1, and OP2. In the CIP rules (Cahn-Ingold-Prelog, [25,26] …”
Section: Notation For Assignment Ambiguitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of antitumor activity and tubulin binding studies of a large number of cholchicinoids had indicated the importance of the spatial arrangement of the four methoxy groups in the drug-protein interaction, the mechanism of interaction is still not clearly understood. A recent report [6] Note: The italic letter a before the corresponding R and S denotes an axial chirality originating from a biaryl system as suggested by Calm et al [1] with the protein would therefore deserve special attention. Support for this hypothesis has now been …”
Section: Introductionmentioning
confidence: 99%